Humor as a Dispositional Property: Toward a Metaphysical Grounding from Analytic Functionalism - Téllez Aguilar, Alexander (2026)
The article argues that humor is not a mental state in the strict sense but a dispositional property of certain mental states, activated by the incongruity between the expected representational content and the object's actual presentation. Classical theories (superiority, relief, and incongruity) are critically reconstructed to expose their explanatory limits, and Lewis's analytic functionalism is deployed within a non-reductive physicalist framework. This grounding accounts for humor's contextual variability by appeal to the agent's cognitive structures, and it opens projections toward the ethics of humor and the clinical study of its impairments.